1996
DOI: 10.1139/m96-080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial communities in heavy metal contaminated soils

Abstract: Heavy metal pollution is a principle source of environmental contamination. We analyzed heavy metal impacted soil microbial communities and found that, in general, although lead adversely affected biomass, metabolic activity, and diversity, autochthonous lead- and cadmium-resistant isolates were found. In several metal-stressed soils, the microbial community consisted of two populations, either resistant or sensitive to lead. Additionally, a lead-resistant isolate was isolated from a control soil with no known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 20 publications
6
100
1
Order By: Relevance
“…Chromosome and plasmid encoded metal resistance genetic systems have been studied in Pseudomonas, as well as in related bacteria (Cervantes, 1996). Pseudomonas species resistant to cadmium up to 1.2 mM maximum tolerable concentration was isolated from heavy metal contaminated soil (Roane and Kellogg, 1996). P. aeruginosa BC15 resistant to cadmium up to 6 mM in LB agar plates (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…Chromosome and plasmid encoded metal resistance genetic systems have been studied in Pseudomonas, as well as in related bacteria (Cervantes, 1996). Pseudomonas species resistant to cadmium up to 1.2 mM maximum tolerable concentration was isolated from heavy metal contaminated soil (Roane and Kellogg, 1996). P. aeruginosa BC15 resistant to cadmium up to 6 mM in LB agar plates (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…Other results concluded that the frequency of tolerant bacteria increases with an increase of heavy metal concentrations in contaminated soil (Angle et al, 1993;Kunito et al, 2001). The frequency of metal resistance bacteria to metal ions reflect the degree of environmental contamination with these heavy metals and may be directly related to exposure of bacteria to them (Roane and Kellogg, 1996;Hassen et al, 1998;Malik and Jaiswal, 2000). The MICs estimated for Cu, Cd, pb, Zn, Hg, Ni, Co, Cr, As, and Te for bacterial isolates in the contaminated soil as well as in the nonuncontaminated soil were at the levels regarded as those typical for metal-resistant species (Kunito, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…The concentration of metal pollutants in the environment is usually low excluding in specific areas, which are polluted by various hospitals and industrial wastes. The concentration of heavy metals is very high in ore containing and mining areas (Roane et al, 1996). This has led to growing concern about the consequence of toxic metals as environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%